Evaluating the Efficacy of Topical Moringa Oleifera and Aloe Vera Extracts in Accelerating Second-Degree Burn Wound Healing - Fauziah, Dwi Nur; Ramadani, Nur Laili; Moniz, Argita Agnesia; Syafitri, Wahyu Fauziah Iga; Humairah, Sandrina; Pradipta, Rifky Octavia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Burn injuries are a global health issue, particularly second-degree burns, which damage both the epidermis and dermis. This has led to the exploration of natural treatments like Moringa oleifera (moringa) and Aloe vera for their potential in wound healing, pain relief, and infection prevention. This study aimed to evaluate the efficacy of a topical formulation containing extracts of Moringa oleifera and Aloe vera in accelerating the healing of second-degree burn wounds. This study employed a true experimental design with Sprague Dawley rats, divided into four groups (control positive, control negative, and two treatment groups). The experiment utilized topical formulations combining different concentrations of Moringa oleifera and Aloe vera extracts. The wound healing process was assessed through macroscopic observation and histopathological analysis, measuring the diameter of the burn wounds at different time intervals. Results showed that formulations containing Moringa oleifera and Aloe vera extracts significantly improved wound healing compared to the control group. The formulation with a 50:50 ratio of Moringa oleifera and Aloe verademonstrated the highest efficacy, reducing wound size and promoting fibroblast proliferation and vascularization. This study confirms the potential of a topical combination of Moringa oleifera and Aloe vera extracts in accelerating the healing of second-degree burns.